PENGARUH FINANCIAL LEVERAGE, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP UNDERPRICING SAHAM SYARIAH SAAT INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA PADA MASA PANDEMI COVID-19 - Apriliani, Siti Raihan; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to determine and analyze the effect of financial leverage, company size, and institutional ownership on the underpricing of sharia shares during the Initial Public Offering (IPO) during the Covid-19 pandemic on the Indonesia Stock Exchange. The population in this study were all companies that made initial public offerings during the Covid-19 pandemic in Indonesia, namely 2020-2021. The sample selection used purposive sampling technique with predetermined criteria so as to get a sample of 50 companies. The research conducted is quantitative research with the type of research data, namely secondary data. Data analysis used multiple linear regression analysis with the help of SPSS 23 data processing application. The results of this study indicate that either simultaneously or partially financial leverage, company size, and institutional ownership variables have no effect on underpricing of sharia shares.